Pengaruh Good Corporate Governance Dan Karakteristik Spesifik Perusahaan Terhadap Restatement - Sevira Rahma Harmara; Fitra Dharma (International Forum of Researchers and Lecturers, 2023)
This research aims to analyze and determine the influence of each variable of auditor change, ownership concentration, number of audit committee meetings, company size, profitability and liquidity on restatement cases in non-financial institutional companies listed on the IDX in 2017-2021. The sample used in this research was 76 companies. The research results show that; changing auditors has a significant negative effect on restatements in non-financial companies listed on the IDX; the number of audit committee meetings has a significant negative effect on restatements in non-financial companies listed on the IDX; ownership concentration has a significant negative effect on restatements in non-financial companies listed on the IDX; company size has a significant positive effect on restatement in non-financial companies listed on the IDX; profitability has a positive and insignificant effect on restatement in non-financial companies listed on the IDX; and Liquidity has a significant negative effect on restatement in non-financial companies listed on the IDX.